Polyarylate fabric whole-core flame-retardant conveying belt and manufacturing method thereof

By adopting a combination of polyaryl fabric whole core structure and specific cover layer and tape-core impregnated adhesive, the existing flame retardant conveyor belts are solved in terms of strength and cost, and high strength, low cost and good flame retardant performance are achieved, which is suitable for safe and economical transportation of coal underground in coal mines.

CN119798885APending Publication Date: 2025-04-11ANHUI ZHONGYI RUBBER BELTS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510066983.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing flame retardant conveyor belts for coal mines have shortcomings in terms of strength and cost. The joint time of the wire rope core flame retardant conveyor belt is long and the quality is difficult to control, while the aramid fabric core flame retardant conveyor belt has high cost and fast strength attenuation.

Method used

The polyaryl fabric whole core structure is adopted, and the integrated braided structure of liquid crystal polyaryl fiber, nylon fiber and cotton fiber is combined with a specific cover layer and core impregnated rubber to achieve a high-strength and low-cost flame retardant conveyor belt.

Benefits of technology

It achieves high strength, low cost and good flame retardant performance, can meet the safe and economical transportation needs of coal underground in coal mines, and simplifies manufacturing processes and reduces energy consumption and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244558820000151
    Figure BDA0005244558820000151
  • Figure BDA0005244558820000161
    Figure BDA0005244558820000161
Patent Text Reader

Abstract

The invention discloses a polyarylate fabric whole-core flame-retardant conveying belt and a manufacturing method thereof. The manufacturing method comprises the following steps: dipping and plasticizing a polyarylate fabric whole belt core in a belt core dipping sizing material to obtain a plasticized belt core; the covering layer is dynamically vulcanized and then attached to the plasticized belt core in a thermal state, and the polyarylate fabric whole-core flame-retardant conveying belt is obtained. The polyarylate fabric integral belt core force-bearing line is made of polyarylate fibers, the strength is high, the belt body is thin, the weight is light, the weight of a finished product belt is about 50% of that of a steel wire rope core conveying belt with the same strength, and the energy consumption in the running process of the conveying belt can be greatly reduced; the polyarylester is low in price, good in fatigue resistance, high in impregnation degree with the belt core impregnation sizing material, good in flame retardant property, safe and economical.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conveyor belts, and in particular relates to a polyarylate fabric whole-core flame-retardant conveyor belt and a manufacturing method thereof. Background Art

[0002] The flame-retardant conveyor belts used in coal mines in my country are mainly fabric core flame-retardant conveyor belts of MT / T914 standard and steel cord conveyor belts of MT / T668 standard. In the prior art, fabric whole core flame-retardant conveyor belts have good flame-retardant properties, low production costs, mechanical joints, convenient maintenance and replacement, and are the safest to use. However, since the belt core is subjected to force using polyester or nylon fibers, the strength is relatively low. When the full-thickness tensile strength is required to be above 2500N / mm, fabric whole core flame-retardant conveyor belts are rarely used. Although steel cord flame-retardant conveyor belts can meet the tensile strength requirements, the vulcanization joint time is long, the quality is difficult to control, and they are prone to longitudinal tearing. In addition, steel cord flame-retardant conveyor belts cannot be melted when ignited, which will cause a larger fire.

[0003] The aramid fabric core flame retardant conveyor belt uses a single-layer aramid impregnated canvas with straight warp and weft as the belt core, which has high strength. Compared with the steel rope core flame retardant conveyor belt with the same strength, the belt body is thin and light, which can reduce the energy consumption of the conveyor. However, due to the high price of aramid fiber and poor bending fatigue resistance, the strength decays rapidly during use, and the flame retardant performance is not good after stripping the covering layer. It is used for transporting coal underground in coal mines, which has high cost, large strength loss, and certain safety risks. In addition, the aramid fabric core flame retardant conveyor belt of MT / T914 standard can only use vulcanized joints, which are complicated to operate and take a long time to construct. When used as a chute belt, frequent joints will affect production.

[0004] Patent CN107177115A discloses an energy-saving fabric whole-core flame-retardant conveyor belt and its manufacturing method. By selecting powdered butadiene rubber / chlorinated polyethylene / thermoplastic polyurethane elastomer as the main material of the covering layer and adding additives to reduce the loss factor, the running resistance of the conveyor belt is reduced. By using aramid fiber and polyester fiber together, the strength is high and the belt body is thin; however, this solution reduces the amount of wear by reducing the mass and reducing the loss factor without reducing the tensile strength, and the strength improvement of the flame-retardant conveyor belt is small. Summary of the invention

[0005] One of the purposes of the present invention is to overcome the shortcomings of the prior art, replace the steel cord core flame retardant conveyor belt and the aramid fabric core flame retardant conveyor belt, meet the needs of safe and economical transportation of coal in coal mines, and provide a polyarylate fabric whole core flame retardant conveyor belt.

[0006] The second purpose of the present invention is to solve the problem of how to make the manufacturing process of the polyarylate fabric whole core conveyor belt simple, easy to manufacture, low energy consumption and high production efficiency, and to provide a method for manufacturing a polyarylate fabric whole core flame retardant conveyor belt.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A polyarylate fabric integral core flame retardant conveyor belt comprises a polyarylate fabric integral belt core, a covering layer and a belt core impregnated with rubber material.

[0009] The covering layer comprises the following components by mass:

[0010] 30-45 parts of polyvinyl chloride resin (PVC), 25-40 parts of ethylene propylene diene monomer (EPDM), 12-18 parts of thermoplastic polyurethane elastomer (TPU), 12-18 parts of styrene-ethylene / propylene-styrene block copolymer (SEPS), 2-5 parts of zinc oxide, 1.4-2 parts of stearic acid, 0.3-0.6 parts of sulfur, 2.4-3 parts of diisopropyl peroxide, 1.2-1.8 parts of triallyl isocyanate Cyanurate (TAIC), 0.3-0.6 parts of accelerator M, 0.5-0.8 parts of accelerator TMTD, 1.5-1.8 parts of antioxidant, 18-21 parts of carbon black, 5-8 parts of antimony trioxide, 32-38 parts of hybrid flame retardant materials, 14-20 parts of dioctyl terephthalate (DOP), 6-12 parts of phosphate flame retardant, 5-8 parts of paraffin oil, 2-5 parts of antistatic agent and 2-5 parts of calcium zinc composite stabilizer.

[0011] Further, the antistatic agent is any one of antistatic agent SN, antistatic agent P, antistatic agent k101, and antistatic agent AW-1.

[0012] Further, the phosphate flame retardant is any one of toluene diphenyl phosphate (CDP), diphenyl phosphate (BDP), trioctyl phosphate (TOP) and trichloroethyl phosphate (TCEP).

[0013] Further, the carbon black is any one of N220, N234, N330 and N358.

[0014] Furthermore, the polyarylate fabric integral belt core is a 4-5 layer integral woven structure composed of liquid crystal polyarylate (LCP) fibers, nylon fibers and cotton fibers, and the width is 104-106% of the belt width.

[0015] Furthermore, the warp force lines of the polyarylate fabric integral belt core are formed by plying 1000D or 1500D high-strength liquid crystal polyarylate fibers, and the tensile strength of a single fiber after plying is 1500-3500N, and the density is 184-279 fibers / 10cm.

[0016] Furthermore, the weft force-bearing lines of the integral core of the polyarylate fabric are formed by plying 1000D or 1500D nylon fibers and cotton fibers, and the tensile strength of the single weft line after plying is 450-1250N / line, and the density is 124-160 lines / 10cm.

[0017] Furthermore, the upper and lower warp threads of the overall polyarylate fabric core are cotton fibers, the middle 2-3 warp threads are liquid crystal polyarylate fibers, the warp content of the core is 10-20%, and the weft content of the core is 35-45%.

[0018] Furthermore, the core impregnated rubber material comprises the following components in parts by mass:

[0019] 100-120 parts of polyvinyl chloride paste resin, 52-58 parts of dioctyl terephthalate, 12-18 parts of epoxy soybean oil, 26-32 parts of phosphate flame retardant, 5-8 parts of antimony trioxide, 8-14 parts of intumescent flame retardant and 2-5 parts of calcium zinc composite stabilizer.

[0020] Further, the phosphate flame retardant is any one of toluene diphenyl phosphate (CDP), diphenyl phosphate (BDP), trioctyl phosphate (TOP) and trichloroethyl phosphate (TCEP).

[0021] Further, the intumescent flame retardant is any one of ammonium polyphosphate (APP), melamine polyphosphate (MPP), melamine cyanurate (MCA) and melamine phosphinate (MHP).

[0022] Further, the core impregnated rubber material is prepared by the following steps:

[0023] Add polyvinyl chloride paste resin, dioctyl terephthalate, epoxy soybean oil, phosphate flame retardant, antimony trioxide, intumescent flame retardant and calcium zinc composite stabilizer into a high-speed disperser in sequence, with a stirrer speed of 2500-2900rpm and a stirring time of 20-30min, then grind 2-3 times with a three-roll grinder with a roller distance of 0.15-0.25mm and a rotation speed of 500-750rpm, and after grinding, place in a vacuum degassing machine for degassing for 20-30min with a vacuum degree of -0.05Mpa to -0.085MPa to obtain a core impregnated rubber material.

[0024] A method for manufacturing a polyarylate fabric whole-core flame-retardant conveyor belt comprises the following steps:

[0025] Step 1: The polyarylate fabric integral belt core is impregnated at a speed of 0.6-1.2 m / min through an impregnation tank and a vacuum box filled with belt core impregnation rubber, the vacuum degree is -0.05 MPa to -0.085 MPa, and then enters a plasticizing box for plasticization, the plasticizing temperature is 160-175°C, and the speed of the belt core in the plasticizing box is 0.6-1.2 m / min to obtain a plasticized belt core.

[0026] Step 2: The covering layer is dynamically vulcanized through two extruders and a mold at a speed of 20-60 rpm, and is directly bonded to the plasticized belt core in a hot state. The thickness of the covering layer is 6-8 mm, the extruder speed is 50-60 rpm, the extruder temperature is 160-175°C, the mold temperature is 160-175°C, and the belt core surface temperature is 145-165°C to obtain a polyarylate fabric whole-core flame-retardant conveyor belt.

[0027] Further, the covering layer is prepared by the following steps:

[0028] The hybrid flame retardant masterbatch, preplasticized material, thermoplastic polyurethane elastomer, styrene-ethylene / propylene-styrene block copolymer, zinc oxide, stearic acid, sulfur, diisopropylbenzene peroxide, triallyl isocyanurate, accelerator M, accelerator TMTD, antioxidant, carbon black, phosphate flame retardant and paraffin oil are sequentially added into an internal mixer for mixing, the internal mixer speed is 40-60rpm, and the dynamic vulcanization is carried out at a temperature of 170-175°C for 3-4min, and then passed through a twin-screw extruder with a screw speed of 50-70rpm, and dynamically vulcanized at 170-175°C for 5-6min, granulated, cooled, and a covering layer is obtained.

[0029] Further, the hybrid flame retardant masterbatch is prepared by the following steps:

[0030] Add the hybrid flame retardant material into an internal mixer at 40-60 rpm, heat to 70-80°C, add EPDM rubber and blend for 4-5 minutes, discharge the rubber at 140-145°C, sheet out, cool to room temperature, and stand for 8 hours to obtain a hybrid flame retardant masterbatch.

[0031] Furthermore, the hybrid flame retardant material is prepared by the following steps:

[0032] Expanded graphite (EG), diethylaluminum hypophosphite (ADP), melamine cyanurate (MCA) and ZI F-8 powder are put into a kneader for heating and stirring at a stirring speed of 350-400 rpm. The mixture is heated to 40-60° C., 1-ethyl-3-methylimidazole dimethyl phosphate is sprayed, and heating and stirring are continued. The mixture is stirred at a temperature of 105-110° C. for 10-15 minutes, and a hybrid flame retardant material is obtained after cooling.

[0033] Furthermore, the mass ratio of expanded graphite, diethyl aluminum hypophosphite, melamine cyanurate, ZI F-8 powder and 1-ethyl-3-methylimidazole dimethyl phosphate is 30-35:30-35:20-25:2-3:1.5-2.5.

[0034] Further, the pre-plasticized material is prepared by the following steps:

[0035] Add polyvinyl chloride resin, dioctyl terephthalate, antimony trioxide, antistatic agent and calcium zinc composite stabilizer into a high-speed kneader in sequence, with a mixing speed of 1200-1400rpm, mix at a temperature of 135-145°C for 10-15min, discharge and cool to obtain a pre-plasticized material.

[0036] Beneficial effects of the present invention:

[0037] (1) The polyarylate fabric integral belt core force lines of the present invention are made of polyarylate fibers, which have high strength, thin belt body, and light weight. The weight of the finished belt is about 50% of that of a steel cord conveyor belt with the same strength, which can greatly reduce the energy consumption during the operation of the conveyor belt. Polyarylate is low in price and has good fatigue resistance. It has a high degree of impregnation with the belt core impregnation rubber material, has good flame retardancy, and is safe and economical.

[0038] (2) The covering layer of the present invention is composited with expanded graphite, diethylaluminum hypophosphite, melamine cyanurate, and ZIF-8 powder, which is first surface treated with 1-ethyl-3-methylimidazole dimethyl phosphate and then blended with ethylene propylene rubber. The prepared covering layer has excellent flame retardant, antistatic and mechanical properties, and forms a flame retardant system with antimony trioxide and phosphate flame retardant, which has a synergistic effect and can simultaneously improve the flame retardant, antistatic and mechanical properties of the covering layer. The addition of styrene-isoprene-styrene block copolymer improves the compatibility of the hybrid flame retardant masterbatch and reduces the processing temperature of the blend, thereby improving the flame retardant, mechanical properties and processing performance of the conveyor belt.

[0039] (3) The present invention effectively improves the flame retardant properties of the covering layer by adding ZI F-8 powder, effectively reduces the emission of toxic gases, promotes the rubber to form a denser carbon layer, promotes carbonization to isolate heat and oxygen, improves flame retardant safety, and prevents the agglomeration of hybrid flame retardant materials, thereby improving the compatibility and dispersibility between the hybrid flame retardant material and rubber, and improving the thermal stability, electrical conductivity and mechanical properties of the rubber.

[0040] (4) The present invention uses 1-ethyl-3-methylimidazole dimethyl phosphate instead of silane coupling agent to modify the hybrid flame retardant material, which can reduce the emission of VOCs during the modification and subsequent processing, is beneficial to protecting the environment, improves the dispersibility of the hybrid flame retardant material, and at the same time improves the flame retardant, antistatic and mechanical properties of the conveyor belt.

[0041] (5) The present invention can use either vulcanized joints or mechanical joints. The mechanical joints can be used to quickly install or replace the conveyor belt, reducing downtime. The present invention uses vacuum impregnation of the integral belt core, hot oil carrier heating and plasticization, extruder veneer molding and dynamic vulcanization technology to achieve continuous conveyor belt production. Compared with the production process of steel wire rope core flame retardant conveyor belt and aramid fabric core flame retardant conveyor belt, it saves energy consumption, improves production efficiency, has a simple process and is easy to manufacture. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] Embodiment 1: A flame-retardant conveyor belt made of a polyarylate fabric integral core, comprising a polyarylate fabric integral belt core, a covering layer and a belt core impregnated with rubber.

[0044] The integral belt core of polyarylate fabric is a 4-layer integral woven structure composed of liquid crystal polyarylate (LCP) fiber, nylon fiber and cotton fiber. The warp force lines of the belt core are made of LCP fiber, which is formed by plying 1000D high-strength LCP fiber. The tensile strength of a single strand after plying is 1500N, and the density is 184 strands / 10cm; the upper and lower warp threads of the belt core are cotton fiber, and the middle two warp threads are LCP fiber. The cotton content of the belt core in the warp direction is 20%; the weft force lines of the belt core are made of nylon fiber, and the weft threads are formed by plying 1000D nylon fiber and cotton fiber. The tensile strength of a single strand after plying is 450N / strand, and the density is 160 strands / 10cm; the cotton content of the weft threads of the belt core is 45%.

[0045] A method for preparing a polyarylate fabric whole-core flame-retardant conveyor belt comprises the following steps:

[0046] S1. Put 30 kg of expanded graphite, 30 kg of diethyl aluminum hypophosphite, 20 kg of melamine cyanurate and 2 kg of ZI F-8 powder into a kneader and heat and stir at a stirring speed of 350 rpm. Heat to 40 ° C, start spraying 1.5 kg of 1-ethyl-3-methylimidazole dimethyl phosphate, continue heating and stirring, stir at a temperature of 105 ° C for 10 minutes, and obtain a hybrid flame retardant material after cooling.

[0047] S2. Add 32 kg of hybrid flame retardant material into an internal mixer with a rotor speed of 40 rpm. Heat to 70°C and add 25 kg of EPDM rubber for blending for 4 min. Discharging temperature is 140°C. Discharging the sheet, cooling to room temperature, and leaving for 8 hours to obtain a hybrid flame retardant masterbatch.

[0048] S3. Add 30kg of polyvinyl chloride resin, 14kg of dioctyl terephthalate, 5kg of antimony trioxide, 2kg of antistatic agent SN and 2kg of calcium zinc composite stabilizer into a high-speed kneader in sequence at a mixing speed of 1200rpm, mix at a temperature of 135°C for 10min, discharge and cool to obtain a pre-plasticized material.

[0049] S4. The hybrid flame retardant masterbatch obtained in S2, the preplasticized material obtained in S3, 12kg of thermoplastic polyurethane elastomer, 12kg of styrene-ethylene / propylene-styrene block copolymer, 2kg of zinc oxide, 1.4kg of stearic acid, 0.3kg of sulfur, 2.4kg of diisopropyl peroxide, 1.2kg of triallyl isocyanurate, 0.3kg of accelerator M, 0.5kg of accelerator TMTD, 1.5kg of antioxidant, 18kg of N220, 6kg of toluene diphenyl phosphate and 5kg of paraffin oil are added to an internal mixer in sequence for mixing. The internal mixer speed is 40rpm. Dynamic vulcanization is carried out at a temperature of 170°C for 3min. Then, the mixture is passed through a twin-screw extruder at a screw speed of 50rpm and dynamically vulcanized at 170°C for 5min. Granulation and cooling are carried out to obtain a covering layer.

[0050] S5. Add 100kg of polyvinyl chloride paste resin, 52kg of dioctyl terephthalate, 12kg of epoxy soybean oil, 26kg of toluene diphenyl phosphate, 5kg of antimony trioxide, 8kg of ammonium polyphosphate and 2kg of calcium-zinc composite stabilizer into a high-speed disperser in sequence, stir at high speed at room temperature, with a stirrer speed of 2500rpm and a stirring time of 20min, stir until the viscosity is 4000Pa.s to obtain a paste, grind the paste twice with a three-roll grinder, with a grinder roller spacing of 0.15mm and a rotation speed of 500rpm. After grinding, place it in a vacuum degassing machine for degassing for 20min with a vacuum degree of -0.05Mpa to obtain a core impregnated rubber material.

[0051] S6. Drive the polyarylate fabric integral belt core through an impregnation tank and a vacuum box filled with belt core impregnation rubber at a speed of 0.6 m / min under the drive of a traction machine. The vacuum degree is -0.05 MPa. The impregnated belt core enters a plasticizing box for plasticization at a plasticizing temperature of 160°C. The speed of the belt core in the plasticizing box is 0.6 m / min to obtain a plasticized belt core.

[0052] S7, the covering layer is dynamically vulcanized through two extruders and a mold at a speed of 20rpm, and is directly bonded to the plasticized belt core made by S7 in a hot state. The thickness of the covering layer is 6mm, the extruder speed is 50rpm, the extruder temperature is 160℃, the mold temperature is 160℃, and the belt core surface temperature is 145℃, thereby obtaining a polyarylate fabric whole-core flame-retardant conveyor belt.

[0053] Embodiment 2: A flame-retardant conveyor belt made of a polyarylate fabric integral core, comprising a polyarylate fabric integral belt core, a covering layer and a belt core impregnated with rubber.

[0054] The polyarylate fabric integral belt core is a 4-layer integral woven structure composed of liquid crystal polyarylate (LCP) fiber, nylon fiber and cotton fiber. The warp force line of the belt core adopts LCP fiber, which is formed by plying 1000D high-strength LCP fiber. The single tensile strength after plying is 2000N and the density is 220 strands / 10cm; the upper and lower warp threads of the belt core are cotton fiber, and the middle two warp threads are LCP fiber. The warp cotton content of the belt core is 18%; the weft force line of the belt core adopts nylon fiber, and the weft threads are formed by plying 1000D nylon fiber and cotton fiber. The single tensile strength of the weft threads after plying is 750N / thread and the density is 145 strands / 10cm; the weft threads of the belt core contain 40% cotton.

[0055] A method for preparing a polyarylate fabric whole-core flame-retardant conveyor belt comprises the following steps:

[0056] S1. Put 31 kg of expanded graphite, 31 kg of diethyl aluminum hypophosphite, 21 kg of melamine cyanurate and 2.2 kg of ZIF-8 powder into a kneader, heat and stir at a stirring speed of 350 rpm, heat to 40°C, start spraying 1.7 kg of 1-ethyl-3-methylimidazole dimethyl phosphate, continue heating and stirring, stir at a temperature of 105°C for 10 minutes, and obtain a hybrid flame retardant material after cooling.

[0057] S2. Add 36 kg of hybrid flame retardant material into an internal mixer with a rotor speed of 40 rpm. After heating to 70°C, add 35 kg of EPDM rubber and blend for 4 minutes. The rubber discharge temperature is 140°C. Discharge the sheet, cool to room temperature, and leave for 8 hours to obtain a hybrid flame retardant masterbatch.

[0058] S3. Add 35 kg of polyvinyl chloride resin, 16 kg of dioctyl terephthalate, 7 kg of antimony trioxide, 3 kg of antistatic agent P and 3 kg of calcium zinc composite stabilizer into a high-speed kneader in sequence at a mixing speed of 1200 rpm, mix at a temperature of 135°C for 10 min, discharge and cool to obtain a pre-plasticized material.

[0059] S4. The hybrid flame retardant masterbatch obtained in S2, the preplasticized material obtained in S3, 14 kg of thermoplastic polyurethane elastomer, 16 kg of styrene-ethylene / propylene-styrene block copolymer, 4 kg of zinc oxide, 1.8 kg of stearic acid, 0.5 kg of sulfur, 2.8 kg of diisopropyl peroxide, 1.6 kg of triallyl isocyanurate, 0.5 kg of accelerator M, 0.7 kg of accelerator TMTD, 1.7 kg of antioxidant, 20 kg of N234, 10 kg of diphenyl phosphate and 7 kg of paraffin oil are added to an internal mixer in sequence for mixing. The internal mixer speed is 40 rpm. The mixture is dynamically vulcanized at a temperature of 170°C for 3 min. The mixture is then passed through a twin-screw extruder at a screw speed of 50 rpm and dynamically vulcanized at 170°C for 5 min. The mixture is granulated and cooled to obtain a covering layer.

[0060] S5. Add 110kg of polyvinyl chloride paste resin, 54kg of dioctyl terephthalate, 16kg of epoxy soybean oil, 28kg of diphenyl phosphate, 6kg of antimony trioxide, 12kg of melamine polyphosphate and 3kg of calcium zinc composite stabilizer into a high-speed disperser in sequence, stir at high speed at room temperature, with a stirrer speed of 2500rpm and a stirring time of 20min, stir until the viscosity is 4000Pa.s to obtain a paste, grind the paste twice with a three-roll grinder, with a grinder roller spacing of 0.15mm and a rotation speed of 500rpm. After grinding, place it in a vacuum degassing machine for degassing for 20min, with a vacuum degree of -0.05Mpa to obtain a core impregnated rubber compound.

[0061] S6. Drive the polyarylate fabric integral belt core through an impregnation tank and a vacuum box filled with belt core impregnation rubber at a speed of 0.6 m / min under the drive of a traction machine. The vacuum degree is -0.05 MPa. The impregnated belt core enters a plasticizing box for plasticization at a plasticizing temperature of 160°C. The speed of the belt core in the plasticizing box is 0.6 m / min to obtain a plasticized belt core.

[0062] S7, the covering layer is dynamically vulcanized through two extruders and a mold at a speed of 20rpm, and is directly bonded to the plasticized belt core made by S7 in a hot state. The thickness of the covering layer is 6mm, the extruder speed is 50rpm, the extruder temperature is 160℃, the mold temperature is 160℃, and the belt core surface temperature is 145℃, thereby obtaining a polyarylate fabric whole-core flame-retardant conveyor belt.

[0063] Example 3: A flame-retardant conveyor belt made of a polyarylate fabric integral core, comprising a polyarylate fabric integral belt core, a covering layer and a belt core impregnated with rubber.

[0064] The polyarylate fabric integral belt core is a 5-layer integral woven structure composed of LCP fiber, nylon fiber and cotton fiber. The warp force line of the belt core adopts LCP fiber, which is made of 1500D high-strength LCP fiber. The tensile strength of a single strand after plying is 2500N and the density is 238 strands / 10cm; the upper and lower warp threads of the belt core are cotton fiber, and the middle three warp threads are LCP fiber. The cotton content of the belt core in the warp direction is 15%; the weft force line of the belt core adopts nylon fiber, and the weft thread is made of 1500D nylon fiber and cotton fiber. The tensile strength of a single strand after plying is 900N / strand and the density is 138 strands / 10cm; the cotton content of the weft thread of the belt core is 37%;

[0065] A method for preparing a polyarylate fabric whole-core flame-retardant conveyor belt comprises the following steps:

[0066] S1. 32.5 kg of expanded graphite, 32.5 kg of diethyl aluminum hypophosphite, 22.5 kg of melamine cyanurate and 2.5 kg of ZI F-8 powder were put into a kneader and heated and stirred at a stirring speed of 375 rpm. The mixture was heated to 50 ° C. 2 kg of 1-ethyl-3-methylimidazole dimethyl phosphate was sprayed. The heating and stirring were continued. The mixture was stirred at a temperature of 107 ° C for 12.5 min. After cooling, a hybrid flame retardant material was obtained.

[0067] S2. Add 35 kg of hybrid flame retardant material into an internal mixer with a rotor speed of 50 rpm. After heating to 75°C, add 34 kg of EPDM rubber and blend for 4.5 min. The rubber discharge temperature is 142.5°C. Discharge the sheet, cool to room temperature, and leave for 8 hours to obtain a hybrid flame retardant masterbatch.

[0068] S3. Add 38kg of polyvinyl chloride resin, 17kg of dioctyl terephthalate, 6.5kg of antimony trioxide, 3.5kg of antistatic agent K101 and 3.5kg of calcium zinc composite stabilizer into a high-speed kneader in sequence at a mixing speed of 1300rpm, mix at a temperature of 140°C for 12.5min, discharge and cool to obtain a pre-plasticized material.

[0069] S4. The hybrid flame retardant masterbatch obtained in S2, the preplasticized material obtained in S3, 15 kg of thermoplastic polyurethane elastomer, 15 kg of styrene-ethylene / propylene-styrene block copolymer, 3.5 kg of zinc oxide, 1.7 kg of stearic acid, 0.45 kg of sulfur, 2.7 kg of diisopropyl peroxide, 1.5 kg of triallyl isocyanurate, 0.45 kg of accelerator M, 0.65 kg of accelerator TMTD, 1.65 kg of antioxidant, 19.5 kg of N330, 9 kg of trioctyl phosphate and 6.5 kg of paraffin oil are added to an internal mixer in sequence for mixing. The internal mixer speed is 50 rpm. The mixture is dynamically vulcanized at a temperature of 172.5°C for 3.5 min. The mixture is then passed through a twin-screw extruder at a screw speed of 60 rpm and dynamically vulcanized at 172.5°C for 5.5 min. The mixture is granulated and cooled to obtain a covering layer.

[0070] S5. Add 110kg of polyvinyl chloride paste resin, 55kg of dioctyl terephthalate, 15kg of epoxy soybean oil, 29kg of trioctyl phosphate, 6.5kg of antimony trioxide, 11kg of melamine cyanurate and 3.5kg of calcium zinc composite stabilizer into a high-speed disperser in sequence, stir at high speed at room temperature, with a stirrer speed of 2750rpm and a stirring time of 25min, stir until the viscosity is 5000Pa.s to obtain a paste, grind the paste twice with a three-roll grinder with a roller spacing of 0.2mm and a rotation speed of 650rpm, and place it in a vacuum degassing machine for degassing for 25min after grinding with a vacuum degree of -0.07Mpa to obtain a core impregnated rubber compound.

[0071] S6. Drive the polyarylate fabric integral belt core through an impregnation tank and a vacuum box filled with belt core impregnation rubber at a speed of 0.9 m / min under the drive of a traction machine. The vacuum degree is -0.07 MPa. The impregnated belt core enters a plasticizing box for plasticization at a plasticizing temperature of 170°C. The speed of the belt core in the plasticizing box is 0.9 m / min to obtain a plasticized belt core.

[0072] S7, the covering layer is dynamically vulcanized through two extruders and a mold at a speed of 40rpm, and is directly bonded to the plasticized belt core made by S7 in a hot state. The thickness of the covering layer is 7mm, the extruder speed is 55rpm, the extruder temperature is 170℃, the mold temperature is 170℃, and the belt core surface temperature is 155℃, thereby obtaining a polyarylate fabric whole-core flame-retardant conveyor belt.

[0073] Example 4: A flame-retardant conveyor belt made of a polyarylate fabric integral core, comprising a polyarylate fabric integral belt core, a covering layer and a belt core impregnated with rubber.

[0074] The polyarylate fabric integral belt core is a 5-layer integral woven structure composed of LCP fiber, nylon fiber and cotton fiber. The warp force line of the belt core adopts LCP fiber, which is made of 1500D high-strength LCP fiber. The tensile strength of a single strand after plying is 3000N and the density is 231 strands / 10cm; the upper and lower warp threads of the belt core are cotton fiber, and the middle three warp threads are LCP fiber. The cotton content of the belt core in the warp direction is 12%; the weft force line of the belt core adopts nylon fiber, and the weft thread is made of 1500D nylon fiber and cotton fiber. The tensile strength of a single strand after plying is 1050N / strand and the density is 133 strands / 10cm; the cotton content of the weft thread of the belt core is 36%;

[0075] A method for preparing a polyarylate fabric whole-core flame-retardant conveyor belt comprises the following steps:

[0076] S1. Put 34 kg of expanded graphite, 34 kg of diethyl aluminum hypophosphite, 24 kg of melamine cyanurate and 2.8 kg of ZIF-8 powder into a kneader and heat and stir at a stirring speed of 400 rpm. Heat to 60° C. and start spraying 2.4 kg of 1-ethyl-3-methylimidazole dimethyl phosphate. Continue heating and stirring. Stir at a temperature of 110° C. for 15 minutes. After cooling, obtain a hybrid flame retardant material.

[0077] S2. Add 35 kg of hybrid flame retardant material into an internal mixer with a rotor speed of 60 rpm. After heating to 80°C, add 38 kg of EPDM rubber and blend for 5 minutes. The rubber discharge temperature is 145°C. Discharge the sheet, cool to room temperature, and leave for 8 hours to obtain a hybrid flame retardant masterbatch.

[0078] S3. Add 42kg of polyvinyl chloride resin, 15kg of dioctyl terephthalate, 6kg of antimony trioxide, 3kg of antistatic agent AW-1 and 4kg of calcium zinc composite stabilizer into a high-speed kneader in sequence at a mixing speed of 1400rpm, mix at a temperature of 145°C for 15min, discharge and cool to obtain a pre-plasticized material.

[0079] S4. The hybrid flame retardant masterbatch obtained in S2, the preplasticized material obtained in S3, 15 kg of thermoplastic polyurethane elastomer, 15 kg of styrene-ethylene / propylene-styrene block copolymer, 4 kg of zinc oxide, 1.5 kg of stearic acid, 0.5 kg of sulfur, 2.5 kg of diisopropyl peroxide, 1.5 kg of triallyl isocyanurate, 0.5 kg of accelerator M, 0.6 kg of accelerator TMTD, 1.6 kg of antioxidant, 20 kg of N358, 15 kg of trichloroethyl phosphate and 6 kg of paraffin oil are added to an internal mixer in sequence for mixing. The internal mixer speed is 60 rpm. Dynamic vulcanization is carried out at a temperature of 175°C for 4 min. Then, it is passed through a twin-screw extruder with a screw speed of 70 rpm and dynamically vulcanized at 175°C for 6 min. Granulation and cooling are carried out to obtain a covering layer.

[0080] S5. Add 115kg of polyvinyl chloride paste resin, 56kg of dioctyl terephthalate, 14kg of epoxy soybean oil, 30kg of trichloroethyl phosphate, 7kg of antimony trioxide, 10kg of melamine phosphite and 4kg of calcium zinc composite stabilizer into a high-speed disperser in sequence, stir at high speed at room temperature, with a stirrer speed of 2900rpm and a stirring time of 30min, stir until the viscosity is 5500Pa.s to obtain a paste, grind the paste three times with a three-roll grinder, with a grinder roller spacing of 0.25mm and a rotation speed of 750rpm. After grinding, place it in a vacuum degassing machine for degassing for 30min with a vacuum degree of -0.085MPa to obtain a core impregnated rubber compound.

[0081] S6. Drive the polyarylate fabric integral belt core obtained in S1 through an impregnation tank and a vacuum box filled with belt core impregnation rubber at a speed of 1.2m / min under the drive of a traction machine. The vacuum degree is -0.085MPa. The impregnated belt core enters a plasticizing box for plasticization at a plasticizing temperature of 175°C. The speed of the belt core in the plasticizing box is 1.2m / min to obtain a plasticized belt core.

[0082] S7, the covering layer is dynamically vulcanized through two extruders and a mold at a speed of 60rpm, and is directly bonded to the plasticized belt core made by S7 in a hot state. The thickness of the covering layer is 8mm, the extruder speed is 60rpm, the extruder temperature is 175℃, the mold temperature is 175℃, and the belt core surface temperature is 165℃, thereby obtaining a polyarylate fabric whole-core flame-retardant conveyor belt.

[0083] Example 5: A flame-retardant conveyor belt made of a polyarylate fabric integral core, comprising a polyarylate fabric integral belt core, a covering layer and a belt core impregnated with rubber.

[0084] The polyarylate fabric integral belt core is a 5-layer integral woven structure composed of LCP fiber, nylon fiber and cotton fiber. The warp force line of the belt core adopts LCP fiber, which is made of 1500D high-strength LCP fiber. The tensile strength of a single strand after plying is 3500N and the density is 236 strands / 10cm; the upper and lower warp threads of the belt core are cotton fiber, and the middle three warp threads are LCP fiber. The cotton content of the belt core in the warp direction is 10%; the weft force line of the belt core adopts nylon fiber, and the weft thread is made of 1500D nylon fiber and cotton fiber. The tensile strength of a single strand after plying is 1250N / strand and the density is 124 strands / 10cm; the cotton content of the weft thread of the belt core is 35%;

[0085] A method for preparing a polyarylate fabric whole-core flame-retardant conveyor belt comprises the following steps:

[0086] S1. Put 35 kg of expanded graphite, 35 kg of diethyl aluminum hypophosphite, 25 kg of melamine cyanurate and 3 kg of ZI F-8 powder into a kneader and heat and stir at a stirring speed of 400 rpm. Heat to 60° C. and start spraying 2.5 kg of 1-ethyl-3-methylimidazole dimethyl phosphate. Continue heating and stirring. Stir at a temperature of 110° C. for 15 min. After cooling, obtain a hybrid flame retardant material.

[0087] S2. Add 38 kg of hybrid flame retardant material into an internal mixer with a rotor speed of 60 rpm. Heat to 80°C and add 40 kg of EPDM rubber for blending for 5 min. Discharging temperature is 145°C. Discharging the sheet, cooling to room temperature, and leaving for 8 hours to obtain a hybrid flame retardant masterbatch.

[0088] S3. Add 45 kg of polyvinyl chloride resin, 20 kg of dioctyl terephthalate, 8 kg of antimony trioxide, 5 kg of antistatic agent and 5 kg of calcium zinc composite stabilizer into a high-speed kneader in sequence at a mixing speed of 1400 rpm, mix at a temperature of 145° C. for 15 min, discharge and cool to obtain a pre-plasticized material.

[0089] S4. The hybrid flame retardant masterbatch obtained in S2, the preplasticized material obtained in S3, 18 kg of thermoplastic polyurethane elastomer, 18 kg of styrene-ethylene / propylene-styrene block copolymer, 5 kg of zinc oxide, 2 kg of stearic acid, 0.6 kg of sulfur, 3 kg of diisopropyl peroxide, 1.8 kg of triallyl isocyanurate, 0.6 kg of accelerator M, 0.8 kg of accelerator TMTD, 1.8 kg of antioxidant, 21 kg of N358, 12 kg of trichloroethyl phosphate and 8 kg of paraffin oil are added to an internal mixer in sequence for mixing. The internal mixer speed is 60 rpm. Dynamic vulcanization is carried out at a temperature of 175°C for 4 min. Then, the mixture is passed through a twin-screw extruder at a screw speed of 70 rpm and dynamically vulcanized at 175°C for 6 min. Granulation and cooling are carried out to obtain a covering layer.

[0090] S5. Add 120kg of polyvinyl chloride paste resin, 58kg of dioctyl terephthalate, 18kg of epoxy soybean oil, 32kg of trichloroethyl phosphate, 8kg of antimony trioxide, 14kg of melamine phosphite and 5kg of calcium zinc composite stabilizer into a high-speed disperser in sequence, stir at high speed at room temperature, with a stirrer speed of 2900rpm and a stirring time of 30min, stir until the viscosity is 5500Pa.s to obtain a paste, grind the paste three times with a three-roll grinder, with a grinder roller spacing of 0.25mm and a rotation speed of 750rpm. After grinding, place it in a vacuum degassing machine for degassing for 30min with a vacuum degree of -0.085MPa to obtain a core impregnated rubber compound.

[0091] S6. Drive the polyarylate fabric integral belt core obtained in S1 through an impregnation tank and a vacuum box filled with belt core impregnation rubber at a speed of 1.2m / min under the drive of a traction machine. The vacuum degree is -0.085MPa. The impregnated belt core enters a plasticizing box for plasticization at a plasticizing temperature of 175°C. The speed of the belt core in the plasticizing box is 1.2m / min to obtain a plasticized belt core.

[0092] S7, the covering layer is dynamically vulcanized through two extruders and a mold at a speed of 60rpm, and is directly bonded to the plasticized belt core made by S7 in a hot state. The thickness of the covering layer is 8mm, the extruder speed is 60rpm, the extruder temperature is 175℃, the mold temperature is 175℃, and the belt core surface temperature is 165℃, thereby obtaining a polyarylate fabric whole-core flame-retardant conveyor belt.

[0093] The polyarylate fabric whole core flame retardant conveyor belts prepared in Examples 1 to 5 were tested according to the standard MT / T 914-2019 to test the physical properties and flame retardant properties of the samples. The results are as follows:

[0094] As shown in Table 1:

[0095]

[0096]

[0097] It can be seen from Table 1 that the polyarylate fabric whole-core flame-retardant conveyor belt prepared in the present invention has excellent longitudinal and transverse full-thickness tensile strength, can be well adapted to application scenarios with requirements above 2500N / mm, and has excellent flame retardancy, antistatic properties and mechanical joint strength.

[0098] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A flame-retardant conveyor belt made of polyarylate fabric, characterized in that: It includes a polyarylate fabric integral belt core, a covering layer and a belt core impregnated with rubber material; The covering layer comprises the following components in parts by mass: 30-45 parts of polyvinyl chloride resin, 25-40 parts of ethylene propylene rubber, 12-18 parts of thermoplastic polyurethane elastomer, 12-18 parts of styrene-ethylene / propylene-styrene block copolymer, 2-5 parts of zinc oxide, 1.4-2 parts of stearic acid, 0.3-0.6 parts of sulfur, 2.4-3 parts of diisopropyl peroxide, 1.2-1.8 parts of triallyl isocyanurate, 0.3-0.6 parts of accelerator M, 0.5-0.8 parts of accelerator TMTD, 1.5-1.8 parts of antioxidant, 18-21 parts of carbon black, 5-8 parts of antimony trioxide, 32-38 parts of hybrid flame retardant material, 14-20 parts of dioctyl terephthalate, 6-12 parts of phosphate flame retardant, 5-8 parts of paraffin oil, 2-5 parts of antistatic agent and 2-5 parts of calcium zinc composite stabilizer.

2. The flame-retardant conveyor belt made of polyarylate fabric as claimed in claim 1, characterized in that: The polyarylate fabric integral belt core is a 4-5-layer integral woven structure composed of liquid crystal polyarylate fibers, nylon fibers and cotton fibers, and the width is 104-106% of the bandwidth; The warp force lines of the polyarylate fabric integral belt core are formed by plying 1000D or 1500D high-strength liquid crystal polyarylate fibers, and the tensile strength of a single fiber after plying is 1500-3500N, and the density is 184-279 fibers / 10cm; The polyarylate fabric integral core weft force lines are formed by plying 1000D or 1500D nylon fibers and cotton fibers, and the tensile strength of the single weft after plying is 450-1250N / thread, and the density is 124-160 threads / 10cm; The upper and lower warp threads of the polyarylate fabric integral belt core are cotton fibers, the middle 2-3 warp threads are liquid crystal polyarylate fibers, the warp content of the belt core is 10-20%, and the weft content of the belt core is 35-45%.

3. The polyarylate fabric whole core flame retardant conveyor belt according to claim 1, characterized in that: The core impregnated rubber material comprises the following components in parts by mass: 100-120 parts of polyvinyl chloride paste resin, 52-58 parts of dioctyl terephthalate, 12-18 parts of epoxy soybean oil, 26-32 parts of phosphate flame retardant, 5-8 parts of antimony trioxide, 8-14 parts of intumescent flame retardant and 2-5 parts of calcium zinc composite stabilizer.

4. The flame-retardant conveyor belt made of a polyarylate fabric as claimed in claim 3, characterized in that: The core impregnated rubber material is prepared by the following steps: Add polyvinyl chloride paste resin, dioctyl terephthalate, epoxy soybean oil, phosphate flame retardant, antimony trioxide, intumescent flame retardant and calcium zinc composite stabilizer into a high-speed disperser in sequence, with a stirrer speed of 2500-2900 rpm and a stirring time of 20-30 min. Then grind it 2-3 times with a three-roll grinder with a roller distance of 0.15-0.25 mm and a rotation speed of 500-750 rpm. After grinding, place it in a vacuum degassing machine for degassing for 20-30 min to obtain a core impregnated rubber material.

5. The method for manufacturing a polyarylate fabric solid core flame retardant conveyor belt according to claim 1, characterized in that: The steps include: Step 1: Pass the polyarylate fabric integral belt core through an impregnation tank and a vacuum box filled with belt core impregnation rubber at a speed of 0.6-1.2 m / min, and then enter the plasticizing box for plasticization at a plasticizing temperature of 160-175° C. The speed of the belt core in the plasticizing box is 0.6-1.2 m / min to obtain a plasticized belt core; Step 2: The covering layer is dynamically vulcanized through two extruders and a mold at a speed of 20-60 rpm, and is directly bonded to the plasticized belt core in a hot state. The thickness of the covering layer is 6-8 mm, the extruder speed is 50-60 rpm, the extruder temperature is 160-175°C, the mold temperature is 160-175°C, and the belt core surface temperature is 145-165°C to obtain a polyarylate fabric whole-core flame-retardant conveyor belt.

6. The method for manufacturing a polyarylate fabric solid core flame retardant conveyor belt according to claim 5, characterized in that: The covering layer is prepared by the following steps: The hybrid flame retardant masterbatch, preplasticized material, thermoplastic polyurethane elastomer, styrene-ethylene / propylene-styrene block copolymer, zinc oxide, stearic acid, sulfur, diisopropylbenzene peroxide, triallyl isocyanurate, accelerator M, accelerator TMTD, antioxidant, carbon black, phosphate flame retardant and paraffin oil are sequentially added into an internal mixer for mixing, the internal mixer speed is 40-60rpm, and the dynamic vulcanization is carried out at a temperature of 170-175°C for 3-4min, and then passed through a twin-screw extruder with a screw speed of 50-70rpm, and dynamically vulcanized at 170-175°C for 5-6min, granulated, cooled, and a covering layer is obtained.

7. The method for manufacturing a polyarylate fabric solid core flame retardant conveyor belt according to claim 4, characterized in that: The hybrid flame retardant masterbatch is prepared by the following steps: Add the hybrid flame retardant material into an internal mixer at 40-60 rpm, heat to 70-80°C, add EPDM rubber and blend for 4-5 minutes, discharge the rubber at 140-145°C, sheet out, cool to room temperature, and stand for 8 hours to obtain a hybrid flame retardant masterbatch.

8. The method for manufacturing a polyarylate fabric solid core flame retardant conveyor belt according to claim 7, characterized in that: The hybrid flame retardant material is prepared by the following steps: Put expanded graphite, diethyl aluminum hypophosphite, melamine cyanurate and ZI F-8 powder into a kneader, heat and stir at a stirring speed of 350-400 rpm, heat to 40-60° C., start spraying 1-ethyl-3-methylimidazole dimethyl phosphate, continue heating and stirring, stir at a temperature of 105-110° C. for 10-15 minutes, and obtain a hybrid flame retardant material after cooling.

9. The method for manufacturing a polyarylate fabric solid core flame retardant conveyor belt according to claim 8, characterized in that: The mass ratio of the expanded graphite, diethylaluminum hypophosphite, melamine cyanurate, ZI F-8 powder and 1-ethyl-3-methylimidazole dimethyl phosphate is 30-35:30-35:20-25:2-3:1.5-2.

5.

10. The method for manufacturing a polyarylate fabric solid core flame retardant conveyor belt according to claim 6, characterized in that: The pre-plasticized material is prepared by the following steps: Add polyvinyl chloride resin, dioctyl terephthalate, antimony trioxide, antistatic agent and calcium zinc composite stabilizer into a high-speed kneader in sequence, with a mixing speed of 1200-1400rpm, mix at a temperature of 135-145°C for 10-15min, discharge and cool to obtain a pre-plasticized material.

Citation Information

Patent Citations

  • Energy-saving textile whole core flame-retardant conveyor belt and method for manufacturing same

    CN107177115A